Integrative management of hematological disorders: a case series on Healzen’s PRO therapeutic protocol - Ahirrao, Apurva; Kadam, Pandurang; Jain, Ria; Dubey, Dharmendra Kumar; Menon, Kavita (International Journal of Research in Medical Sciences, 2024)
Hematological disorders present significant treatment challenges due to their complex etiology and need for personalized management. This case series evaluates the effectiveness of HealZen’s PRO therapeutic protocol (PTP) in managing conditions like immune thrombocytopenic purpura (ITP) and severe anemia through an integrative approach. Five patients were treated at HealZen Clinic, including a pediatric case of acute ITP and four adult patients with severe anemia and related complications. Each patient received a tailored treatment regimen as part of the PTP, which integrated functional nutrition therapy (FNT), platelet therapy, targeted supplementation such as liquid chlorophyll, liquid spirulina, immunoglobulin, Kinotakara foot patch, Carica papaya, and propolis, and supportive therapies with conventional medical care. The case series demonstrated significant improvements across all patients. The pediatric patient with acute ITP experienced a substantial increase in platelet counts, reducing the need for invasive treatments and hospitalizations. In the adult cases, the PTP led to noteworthy enhancements in hemoglobin levels and a decrease in dependency on blood transfusions. Patients reported improvements in overall well-being, symptom management, and reduced frequency of complications. The integrative approach facilitated better patient adherence and satisfaction with the treatment process. HealZen’s PTP appears to be a promising integrative approach for managing hematological disorders, showing beneficial outcomes in both pediatric and adult patients. The combination of conventional and alternative therapies not only improved clinical parameters but also enhanced quality of life. These findings suggest the potential for broader application and warrant further investigation through controlled trials to validate and optimize this holistic treatment strategy.